Wireless power transfer via radiowaves - Shinohara, Naoki 1968- (ISTE-Wiley, 2014)
Annotation
Includes bibliographical references and index. - Print version record
Keywords: Electric power transmission; Radio waves; Radio Waves; Électricité; Transport; Ondes radioélectriques; TECHNOLOGY & ENGINEERING; Mechanical